The Effect of Islamic Attributes and Quality Service on Satisfaction Toward Muslim Tourist Visit to Padang City Indonesia - Yuliviona, Reni; Abdullah, Mokhtar; Alias, Zuraini; a, Ird; Azliyanti, Elfitra (International Journal of Engineering and Technology, 2018)
This study aims to examine the influence of Islamic attributes and quality service to the satisfaction of Muslim tourists visit of Padang city Indonesia. The study was conducted on 100 Muslim tourists with purposive sampling technique. Data analysis techniques in this study through two general stages, namely measurement model and structural model, these two stages will be analyzed using software smart PLS 2.0M3. The results showed that the Islamic attributes and quality service have a positive and significant influence on the Islamic tourist satisfaction of foreign tourists visiting in Padang city.